Children with separated parents their self-esteem, academic performance and coping behaviors. - Martinez, Ma. Cristina
This study aimed to find out the self-esteem, academic performance and coping behaviors of the children of separated parents of the University of the Philippines in the Visayas Miag-ao. A total of thirty (30) respondents from the different divisions of the College of Arts and Sciences participated in the study. The ages of the respondents ranged from 16-21., Two instruments were utilized in this study namely: Rosenberg Self-Esteem Scale and Lazarus and Folkman Ways of Coping Scale. Results showed that children of separated parents are average school performers as determined by their general weighted average for the 1st semester SY 2006-2007. The registered high self-esteem obtaining a score of 26 and above on the Rosenberg Self-Esteem Scale. Finally, they used problem focused behaviors a means of coping mechanism with regards to their parents' separation.